Investigations of Latrine Coverage and Associated Factors Among Debretabor Town, Amhara Region North West Ethiopia - Yilkal Tafere; Mirkuzie Woldie; Henok Assefa (International Journal of Public Health Science (IJPHS), 2016)
Studies in a number of countries have shown that wherever inappropraite waste disposal morbidity and mortality rates are high. Although latrine coverage is an important indicator for measuring success of the health service program; data on latrine coverage scarce in the study area. Objective: To investigate latrine coverage and associated factors in among households of Debretabor town, Amhara region, Ethiopia. Methods: A community based cross sectional study was conducted in Debretabor town from September 1-30, 2013. A total of 422 households were included in the study using systematic sampling technique. Data were collected using structured questionnaire and analyzed using SPSS version 16.0. Degree of association between independent and dependent variables was assessed with a 95% confidence level and p-value less than 0.05 was used to detect statistical significance. Result: In this study. Ninety three point five percent of households have latrine. Graduated as model family was predictor for availability of latrine (AOR= 3.18,). Income and house ownership were also found to be predictors for availability of latrine (AOR=3.70), (AOR=8.46), respectively. Educational status of respondents was found to be predictors for availability of latrine (AOR= 2.65). Conclusion:  latrine coverage was relatively lower from the national target of 100%, still there are households that use open defication. Educational status, house owner shipe, income and graduated as model family were main factors affecting latrine availability. Improving socio economic status of households, provision of continuous advice and technical support at household level on the availability of latrine are recommended.